Cochlear Implantation in Adults with Prelingual Deafness. Part I. Clinical Results - Teoh, Su Wooi (2004)
OBJECTIVES/HYPOTHESIS: To examine the hypothesis that the newer generations of cochlear implants could provide considerable speech understanding to late-implanted, prelingually deaf adult patients. STUDY DESIGN: Retrospective review. METHODS: Speech perception scores of 103 patients with long-term pre-lingual deafness obtained from the recent clinical trials were compared with other previously published results. RESULTS: Unlike patients receiving implants in early childhood, the audiologic performance of most patients with long-term prelingual deafness rapidly approached asymptotic levels within 1 year after implantation. Beginning at 3 months postimplantation, statistically significant improvement was noted in their speech perception scores compared with their preimplant levels. However, the average performance plateau achieved by this group of patients was significantly below the levels published for postlingual patients. No statistically significant differences were observed between the test scores at any testing interval among patients with different devices. CONCLUSIONS: Most patients with long-term prelingual deafness achieve their performance plateau within 1 year after implantation. The results suggest that patient characteristics, rather than device properties, are likely to be the major contributing factor responsible for the observed audiologic outcomes.